Influence of rehacom system programme on hand function in spastic hemiplegic children - Sara Yousef. Elsebahy; Yomna Farag Ahmed; Abdelaziz Ali Sherief (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess the impact of cognitive therapy with the rehacom visual-motor module on the hand function in hemiplegic cerebral palsy children. Method: The randomised case-control study was conducted at Kafrelsheikh University, Egypt, from September 2021 to February 2022, and comprised children aged 6-8 years with spastic hemiplegic cerebral palsy. They were randomised into control group A and intervention group B. Subjects in group A received designed physical therapy and hand function training, while those in group B additionally received visual-motor coordination training with the help of rehacom system. The groups were evaluated for both visual-motor coordination and fine motor skills at baseline and after 6-month training. SPSS version 26 was used to analyse the raw data of the current study. Results: Of the 40 subjects, 20(50%) were in each of the two groups. There were 13(65%) boys and 7(35%) girls with mean age 66±4.01 months in group A, and 9(45%) boys and 11(55%) girls with mean age 67±4.06 months in group B (p>0.05). Both groups showed improvement related to grasping, visual-motor integration and fine motor quotient post-intervention, but improvement in group B was significantly higher on each count(p<0.05). Conclusion: The addition of visual-motor integration programme by rehacom system was found to be more effective than the effect of routine physiotherapy training alone. Keywords: Cerebral palsy, Hemiplegia, Motor skills, Muscle spasticity, Psychomotor performance.